Changes in glycine and leucine transport during red cell maturation in the rat. Issue 2 (April 1990) - Felipe, A.; Viñas, O.; Remesar, X.
Abstract : Both glycine and leucine transport in rat red blood cells have been studied. The glycine uptake showed two different components, one sodium-dependent and another diffusion-like process. In contrast, leucine uptake was sodium independent. Both, Na + -dependent glycine and the overall leucine uptake in red blood cells showed a saturable pattern. Kinetic parameters in reticulocytes were: i) glycine: apparent Km 0.16 mM; Vmax 100.2 nmol/ml ICW/min; ii) leucine: apparent Km 2.11 mM; Vmax 3.88 μmol/ml ICW/min. The erythrocytes kinetic parameters were: i) glycine: apparent Km 0.17 mM; Vmax 9.47 nmol/ml ICW/min; leucine; apparent Km 4.77 mM; Vmax 7.42 μmol/ml ICW/min. The Kd values (sodium independent glycine uptake) were similar in both kind of cells, but the importance of this component in total glycine uptake in erythrocytes was much higher than in reticulocytes. Our results confirm that rat red blood cells have both saturable leucine and Na + -dependent glycine uptake, but some important changes occur during cell maturation.